2012
DOI: 10.1097/cad.0b013e3283503fbc
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin improves the antitumor effect of X-ray irradiation by blocking the NF-κB pathway

Abstract: Curcumin, a phenolic compound from the rhizomes of Curcuma longa, inhibits the growth of a variety of malignant cell types including lymphoma cells. We investigated the role of curcumin in modulating the response of Burkitt's lymphoma cells to ionizing radiation (IR) in vitro and explored the mechanisms that mediated this effect. We treated three Burkitt's lymphoma cell lines with vehicle, curcumin, IR, and curcumin in combination with IR. Cell viability, apoptosis, and cell cycle distribution were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 32 publications
3
38
0
Order By: Relevance
“…These results suggest that the phosphorylation of ATM plays a crucial role in G2/M phase arrest induced by IR and curcumin through the regulation of p53 and p21 cip1 expression. We previously demonstrated that curcumin sensitizes NHL cells to IR-induced apoptosis through decreasing the NF-κB expression and by inhibiting its nuclear localization induced by IR exposure (13). However, the details of the mechanism by which curcumin regulates IR-induced activation of NF-κB remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results suggest that the phosphorylation of ATM plays a crucial role in G2/M phase arrest induced by IR and curcumin through the regulation of p53 and p21 cip1 expression. We previously demonstrated that curcumin sensitizes NHL cells to IR-induced apoptosis through decreasing the NF-κB expression and by inhibiting its nuclear localization induced by IR exposure (13). However, the details of the mechanism by which curcumin regulates IR-induced activation of NF-κB remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was determined with the tetrazolium salt water-soluble tetrazolium salt assay (Roche Diagnostics GmbH, Penzberg, Germany) as previously described (13). The results were expressed as a percentage of cell viability for each concentration of curcumin with respect to the controls.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The apoptosis induced by curcumin was through an amplification of endoplasmic reticulum (ER) stress, which possibly resulted from the accumulation of misfolded nuclear receptor corepressor protein in the ER [83]. In another study, in Burkitt’s lymphoma cell lines, ionizing radiation-induced apoptosis and G 2 /M phase arrest were increased by pretreatment of curcumin through NF-κB pathway [84]. Additionally, in HuT-78 cells (T-cell lymphoma), curcumin-mediated rapid generation of ROS induced apoptosis through modulating different cell survival and cell death pathways [85].…”
Section: Turmeric and Curcuminmentioning
confidence: 99%